2022
DOI: 10.1093/cid/ciac167
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Immune Response to Inactivated Severe Acute Respiratory Syndrome Coronavirus 2 Vaccine in a Cohort of Immunocompromised Patients in Chile

Abstract: Background Inactivated SARS-CoV-2 vaccines have been widely implemented in low- and middle-income countries. However, immunogenicity in immunocompromised patients has not been established. Herein, we aimed to evaluate immune response to CoronaVac vaccine in these patients. Methods This prospective cohort study included 193 participants with five different immunocompromising conditions and 67 controls, receiving two doses of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Similar to our research, a study from Chile showed that immune responses to inactivated COVID-19 vaccines in immunocompromised patients were markedly weaker than those of healthy controls. 21 Further analysis revealed a markedly lower antibody level in patients with CD4 + T-cell counts ≤350 cells per μL, consistent with the finding that CD4 + T-cell count is positively correlated with neutralizing antibody responses to inactivated SARS-CoV-2. 22 , 23 Therefore, a booster dose or dose adjustment might be needed in HIV-infected individuals, especially those with lower CD4 + T-cell counts.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to our research, a study from Chile showed that immune responses to inactivated COVID-19 vaccines in immunocompromised patients were markedly weaker than those of healthy controls. 21 Further analysis revealed a markedly lower antibody level in patients with CD4 + T-cell counts ≤350 cells per μL, consistent with the finding that CD4 + T-cell count is positively correlated with neutralizing antibody responses to inactivated SARS-CoV-2. 22 , 23 Therefore, a booster dose or dose adjustment might be needed in HIV-infected individuals, especially those with lower CD4 + T-cell counts.…”
Section: Discussionsupporting
confidence: 82%
“…persistent HIV-related immunopathology can nevertheless blunt vaccine responses [17][18][19], prompting initial concern that PLWH may respond sub-optimally to COVID-19 immunization. Data from clinical trials [20,21] and real-world studies however [22][23][24][25][26][27], including from our group [28], described strong initial immune responses to two-dose COVID-19 vaccination in PLWH with controlled HIV loads on therapy and preserved CD4+ T-cell counts [20][21][22][23][24]28], though weaker responses have been observed in PLWH who are not receiving therapy or who have CD4+ T-cell counts <200 cells/mm 3 [22,[25][26][27].…”
Section: Introductionmentioning
confidence: 98%
“…Studies in adult patients with secondary immunodeficiencies or immune dysregulation disorders showed reduced antibody responses to 2 doses of CoronaVac. [31][32][33] S-RBD IgG and sVNT results in our study showed 3 doses of CoronaVac elicited antibody response in IEI patients. Eleven of 17 patients with humoral deficiencies in our study opted for CoronaVac.…”
Section: Discussionmentioning
confidence: 79%